Relativistic treatment of spinless particle subject to generalized Tiez-Wei oscillator - Ikot, Akpan N.; Yazarloo, Bentol Hoda; Antia, Akaniynene D.; Hassanabadi, Hassan (Indian journal of physics, 2013)
The solution of Klein–Gordon equation with equal scalar and vector generalized Tiez-Wei potentials is presented for arbitrary l -wave. The energy bound states and unnormalized wave functions are obtained using the Nikiforov–Uvarov method.